Probe-based confocal laser endomicroscopy in the pancreatic duct provides direct visualization of ductal structures and aids in clinical management. Issue 3 (March 2015) - Kahaleh, Michel; Turner, Brian G.; Bezak, Karl; Sharaiha, Reem Z.; Sarkaria, Savreet; Lieberman, Michael; Jamal-Kabani, Armeen; Millman, Jennifer E.; Sundararajan, Subha V.; Chan, Ching; Mehta, Shivani; Widmer, Jessica L.; et al.
Abstract Background Confocal endomicroscopy provides real-time evaluation of various sites and has been used to provide detailed endomicroscopic imaging of the biliary tree. We aimed to evaluate the feasibility and utility of probe-based confocal laser endomicroscopy of the pancreatic duct as compared to cytologic and histologic results in patients with indeterminate pancreatic duct strictures. Methods Retrospective data on patients with indeterminate pancreatic strictures undergoing endoscopic retrograde cholangiopancreatography (ERCP) and confocal endomicroscopy were collected from two tertiary care centres. Real-time confocal endomicroscopy images were obtained during ERCP and immediate interpretation according to the Miami Classification was performed. Results 18 patients underwent confocal endomicroscopy for evaluation of pancreatic strictures from July 2011 to December 2012. Mean pancreatic duct size was 4.2 mm (range 2.2–8 mm). Eight cases were interpreted as benign, 4 as malignant, 4 suggestive of intraductal papillary mucinous neoplasms, and 2 appeared normal. Cytology/histopathology for 15/16 cases showed similar results to confocal endomicroscopy interpretation. Kappa coefficient of agreement between cyto/histopathology and confocal endomicroscopy was 0.8 (p = 0.0001). Pancreatic confocal endomicroscopy changed management in four patients, changing the type of surgery from total pancreatectomy to whipple. Conclusions Confocal endomicroscopy is effective in assisting with diagnosis of indeterminate pancreatic duct strictures as well as mapping of abnormal pancreatic ducts prior to surgery.